Integration principles for the implementation of optimization processes in the structure of the nanosector of the national economy of Ukraine - Pavlov, Kostiantyn; Pavlova, Olena; Ostapenko, Tetiana; Halytsia, Ihor (My University, 2024)
The article examines the development of the third area of the nanoecon-omy – the economy of nanotechnology – and emphasizes the importance of inno-vation for the country’s economic growth. The authors emphasize the need to create a legislative framework to support nanobusiness, the development of tech-nology parks, and tax incentives. The authors also emphasize the importance of Ukraine’s transition to modern scientific and technical systems for integrating nanotechnology into the economy. The processes of regrouping the country’s re-gions and creating new clusters are identified, facilitating the interaction of innova-tive segments of the economies of different regions.
Keywords: nanoeconomy; nanosector; national economy; integration processes; optimization processes; structure of the nanosector; H00; O41; H80